1
$\begingroup$

How can we prove that

$\displaystyle \lim_{n\to\infty} \sum_{k=0}^{n} \frac{{n \choose k}}{n^{k}(k+3)} = e-2$ ?

The only thing that came to my mind was writing out a few terms to see where that could get me, but I'm not able to make much progres. Any help in the form of hints or a solution would be appreciated.

$\endgroup$
4
$\begingroup$

Using $\displaystyle\frac{1}{k+3}=\int_0^1 t^{k+2}\ dt$, you get $$\sum_{k=0}^{n}\frac{\binom{n}{k}}{n^k(k+3)}=\int_0^1 t^2\sum_{k=0}^{n}\binom{n}{k}\frac{t^k}{n^k}\ dt=\int_0^1 t^2\Big(1+\frac{t}{n}\Big)^n\ dt,$$ and the $n\to\infty$ limit of this is $\displaystyle\int_0^1 t^2 e^t\ dt$ which has the expected value.

$\endgroup$
  • $\begingroup$ I don't get how the second integral simplifies into the given expression, could you please provide a little more info? $\endgroup$ – ExtremeRaider May 4 at 6:14
  • $\begingroup$ Do you mean you are not sure why $\sum\limits_{k=0}^{n} \frac{\binom{n}{k}}{n^k(k+3)} =\int_0^1t^2\left(1+\frac{t}{n}\right)^n\, dt$? $\endgroup$ – Minus One-Twelfth May 4 at 6:26
  • 1
    $\begingroup$ @metamorphy sorry, I don't understand what you mean by that... $\endgroup$ – ExtremeRaider May 4 at 6:36
  • 2
    $\begingroup$ @NikilKumar I mean $(a+b)^n=\sum_{k=0}^{n}\binom{n}{k}a^{n-k}b^k$ with $a=1$ and $b=t/n$. $\endgroup$ – metamorphy May 4 at 6:39
  • 1
    $\begingroup$ @metamorphy ohhh that makes a lot more sense. Thanks! $\endgroup$ – ExtremeRaider May 4 at 6:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.